(untitled) - Hearn, Lafcadio (Japan, 1960)
An early Western attempt to decipher the 'outward strangeness' of all things in Japan, and to place the nation and its people in a larger historical context. This is a lyrical work, singing with respect and love, written by someone who truly made himself part of Japan and its culture. "AS by the religion of the household each individual was ruled in every action of domestic life, so, by the religion of the village or district the family was ruled in all its relations to the outer world. Like the religion of the home, the religion of the commune was ancestor-worship. What the household shrine represented to the family, the Shintô parish-temple represented to the community; and the deity there worshipped as tutelar god was called Ujigami, the god of the Uji, which term originally signified the patriarchal family or gens, as well as the family name."